GANGS, YOUTH IDENTITY AND CULTURAL REPRESSION IN EL SALVADOR - Urbina Gaitán, Chester (2013)
The Salvadoran state, in issuing the anti-gang law of 2003, demonstrates little comprehension around the problematic of the adolescence and youth, using stigmatization and repression to avoid any type of personal or group identification that is not in line with what is established.